2020
DOI: 10.21608/ejar.2020.118601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ocimum basilicum leaves powder on immune response of chicken vaccinated against Newcastle Disease Virus

Abstract: In this research, we study the effect of adding the Ocimum basilicum leaves powder (OBLP), as broilers chicken feed additive and study its effects on the innate and adaptive immune responses as well as the antioxidant effects in broilers vaccinated with Newcastle disease virus (NDV) vaccine. A total of 100 one-day old broiler were randomly divided into 4 equal groups, the first group (G1) was served as normal control group, the second group (G2) was served as vaccination control group. Groups 3 (G3) and 4 (G4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…The effectiveness of Estragole against virus infection was reported by Farida and Abdulaziz (59). They found that supplementation of O. basilicum seeds in broiler diets significantly increased the serum hemagglutination inhibition antibody titers and eliminated Infectious Bronchitis Viruses (IBV) and Newcastle Disease (ND).…”
Section: Guppymentioning
confidence: 85%
See 1 more Smart Citation
“…The effectiveness of Estragole against virus infection was reported by Farida and Abdulaziz (59). They found that supplementation of O. basilicum seeds in broiler diets significantly increased the serum hemagglutination inhibition antibody titers and eliminated Infectious Bronchitis Viruses (IBV) and Newcastle Disease (ND).…”
Section: Guppymentioning
confidence: 85%
“…According to Farida and Nahid (59), adding Ocimum basilicum leaves powder to broiler chicken feed improves the innate immune response, as seen by considerable improvements in cells' phagocytic activity of peripheral blood monocyte, lymphoid organs, and lysozyme concentrations. According to ELnaggar and El-Tahawy (60), Adding Ocimum basilicum leaves powder or seed oils to the broiler basal diet boosted the phagocytic index and activity of the macrophages, allowing it to be administered effectively as a natural growth promoter to improve broiler chick development and immunological response.…”
Section: Anti-inflammatory and Immunomodulatory Effect Of Estragolementioning
confidence: 99%
“…La adición de O. basilicum a la ración de pollos de engorde tiene efectos beneficiosos sobre la respuesta inmune innata que se refleja como aumentos significativos en monocitos de sangre periférica, actividad fagocítica, niveles de lisozima y órganos linfoides proporciones de peso corporal especialmente cuando se usa al 1%, pero si se usa al 0,5% podría ser más ventajoso y podría usarse en áreas con un alto riesgo de infección viral, ya que ayudará en maximizando los beneficios de las vacunas (Mohamed y Abd, 2020).…”
Section: Introductionunclassified